Uncertainty in the education sphere of Ukraine: paths to stabilization - Владислав Горбов; Юлія Горбова (Cхід, 2022)
The article is dedicated to understanding uncertainty as a state in which social systems exist in crisis conditions. Today, the need to conduct scientific research to determine the factors and ways that can overcome the state of uncertainty and lead to stabilization is extremely urgent. As an illustration of such phenomena, the system of higher education was chosen, which underwent significant systemic transformations and changes in the daily behavioral practices of various subjects of the educational process in the crisis conditions of the COVID-19 pandemic. The main idea of the article is based on an attempt to record changes in the educational environment in conditions of social uncertainty, to study changes in established behavioral practices of social subjects and the emergence of qualitatively new phenomena that will require further study. Based on empirical research, the authors identify the factors that contribute to the transition of the education system from a state of crisis to a certain stabilization. Such factors include innovative and technological factors (adaptation of the educational environment with the help of various technological support), mental adaptation to unusual everyday practices (remote learning, new forms of communication, increased psycho-emotional stress, etc.). Factors that have a partially destabilizing nature and exacerbate uncertainties are recorded: the difficulty of identifying students, problems in making socially adequate management decisions at the organizational level, limitations of compensatory mechanisms for adaptation of social subjects to a state of uncertainty. The need for scientific research to study the impact of social and technological innovations on the stabilization of social systems, in particular the system of higher education, is being updated.